Program Makan Bergizi Gratis (Mbg): Pertentangan Konstitusional dan Prinsip Maslahah dalam Kebijakan Publik - Syah Awaluddin (Lembaga Pengembangan Kinerja Dosen, 2026)
The Free Nutritious Meal Program (MBG) is one of the Indonesian government's strategic policies aimed at improving the quality of human resources and addressing nutritional disparities. However, the implementation of this program has triggered serious debates in the constitutional and Islamic legal domains. This article analyzes the logic of the MBG program, which is deemed to conflict with the mandate of Article 31 paragraph (4) of the 1945 Constitution concerning the 20% allocation of the State Budget for education, as well as contradicting the principle of maslahah from the perspective of maqāṣid al-syarī'ah and fiqh siyasah. Using a normative-conceptual approach, this research demonstrates that the diversion of the education budget for MBG is potentially unconstitutional as it threatens the fulfillment of the right to education, reduces teacher welfare, and disrupts the teaching and learning process. From the perspective of Islamic law, the program's inclusive nature without clustering contradicts the provisions of zakat distribution which are limited to eight asnaf (recipient categories), and disregards the principles of distributive justice (al-'adalah) and public interest (al-maslahah al-'ammah). This article recommends improvements in governance, refinement of program targeting, and the search for alternative funding sources that do not compromise the education sector.